Project Citizen: A Catalyst for Enhancing Legal Awareness in Vocational Education Students: Studi PTK pada Siswa Kelas X TKR 4 SMK Negeri 2 Probolinggo - Ajeng Setyo Rini; Sri Untari; Didik Sukriono (Journal of Education and Teaching Learning, 2026)
The study was motivated by the low legal awareness of vocational students caused by the dominance of conventional teacher-centered learning methods, the delivery of material tends to be theoretical, and students' habits still often violate school rules. This study aims to increase legal awareness in Pancasila Education learning through the project citizen learning model for class X TKR 4 students of SMK Negeri 2 Probolinggo, and to see how much the increase in students' legal awareness after the implementation of the project citizen learning model. The study was conducted using a qualitative approach with the Classroom Action Research (CAR) method in two cycles on 34 class X TKR 4 students of SMK Negeri 2 Probolinggo. Data were collected through legal awareness knowledge tests, observations, student worksheets, and field notes. The results of the study showed an increase in students' legal awareness knowledge through the project citizen learning model through an increase in posttest results with an average class score reaching 78 and learning completeness of 84.38%, an increase in learning implementation from 76.47% to 94.12%, and high student participation in group discussions during the project implementation. This study concludes that the application of the project citizen learning model in Pancasila Education subjects is effective in improving the quality of learning, changing passive students into active ones, and achieving the expected learning objectives.